Project 2016 LiveLessons (LiveLessons (Indianapolis, Ind.), 2016)
"Project 2016 LiveLessons is an easy-to-understand, but comprehensive, video course that introduces viewers to Project 2016. This course begins with an introduction into Project 2016's interface and perspectives into how Project receives data for calculations, and then outputs it into categories of information. Following common and best practices, this course teaches viewers how to design and configure a project, enter and sequence tasks correctly, create and assign resources, create a realistic schedule, and manage and track the project to its conclusion. The newest features of Microsoft Project 2016 are used to view multiple Time lines, plan and track using snapshots of the schedule as changes occur, and report on progress by exploring the reporting capabilities of Project 2016 and Office 2016."--Resource description page.